Atmospheric Carbon and Transport – America (ACT‐America) Data Sets: Description, Management, and Delivery. Issue 7 (7th July 2021) - Wei, Y.; Shrestha, R.; Pal, S.; Gerken, T.; Feng, S.; McNelis, J.; Singh, D.; Thornton, M. M.; Boyer, A. G.; Shook, M. A.; Chen, G.; Baier, B. C.; et al.
Abstract: The ACT‐America project is a NASA Earth Venture Suborbital‐2 mission designed to study the transport and fluxes of greenhouse gases. The open and freely available ACT‐America data sets provide airborne in situ measurements of atmospheric carbon dioxide, methane, trace gases, aerosols, clouds, and meteorological properties, airborne remote sensing measurements of aerosol backscatter, atmospheric boundary layer height and columnar content of atmospheric carbon dioxide, tower‐based measurements, and modeled atmospheric mole fractions and regional carbon fluxes of greenhouse gases over the Central and Eastern United States. We conducted 121 research flights during five campaigns in four seasons during 2016–2019 over three regions of the US (Mid‐Atlantic, Midwest and South) using two NASA research aircraft (B‐200 and C‐130). We performed three flight patterns (fair weather, frontal crossings, and OCO‐2 underflights) and collected more than 1, 140 h of airborne measurements via level‐leg flights in the atmospheric boundary layer, lower, and upper free troposphere and vertical profiles spanning these altitudes. We also merged various airborne in situ measurements onto a common standard sampling interval, which brings coherence to the data, creates geolocated data products, and makes it much easier for the users to perform holistic analysis of the ACT‐America data products. Here, we report on detailed information of data sets collected, the workflow for data sets including storage and processing of the quality controlled and quality assured harmonized observations, and their archival and formatting for users. Finally, we provide some important information on the dissemination of data products including metadata and highlights of applications of ACT‐America data sets. Plain Language Summary: We describe the data collected and produced by the Atmospheric Carbon and Transport – America mission, including airborne and tower‐based measurements of greenhouse gases (e.g., carbon dioxide and methane) and modeled atmospheric mole fractions and regional carbon fluxes of greenhouse gases over North America. In this paper, we briefly describe the data collections and archival including the instruments and methodology used to generate, manage, and distribute the data, and the significance of these new measurements for the study of the North American carbon cycle. Key Points: Atmospheric Carbon and Transport – America (ACT‐America) provides a unique, weather‐oriented collection of atmospheric CO2, CH4, trace gases, and meteorological properties measurements ACT‐America data are free and open to the public from the Oak Ridge National Laboratory Distributed Active Archive Center (ORNL DAAC) ACT‐America data are uniquely suited to improve the accuracy and precision of regional inverse greenhouse gas (GHG) flux estimates